Notas e resenhas - Osorio, Héctor Hernán González (Revista Paranaense de Desenvolvimento - RPD, 2011)
Empowerment: The politics of Alternative Development, de John Friedmann. Cambridge, Blackwell Publishers, 1992, 205 p.